Comparative incidence of helminths is sheep and cattle on the same pasture - Santiago, Marco Aurélio Miranda; Costa, Ubiratã Cerser da; Benevenga, Sérgio Fauque (Pesquisa Agropecuaria Brasileira, 2014)
The incidence of helminths in sheep and cattle, maintained on the same pasture, was compared in two areas of Rio Grande do Sul, Brazil. Results indicated the possibility of cross infection of species of Cooperia and Trichostrongylus axei. Trichostrongylus colubriformis and Ostertagia circuncincta appeared more in sheep and O. ostertagia and O. lyrata more in cattle. There was no evidence of cross infection by species of Haernonchus, Oesophagostomum, N ematodirus and Bunostomum. The incidence of Capillaria bovis was low but present in both sheep and cattle.